The Influence of Social Media Marketing, Electronic Word of Mouth and Advertising Effectiveness on Purchase Intent Through Brand Awareness - Rimiyati, Hasnah; Maritza Salma Anisa (Indonesian Journal Publisher, 2025)
This research aims to analyze the influence of Social Media Marketing, Electronic Word of Mouth, and Advertising Effectiveness on Purchase Intention through Brand Awareness. The object of this study is potential consumers of Maxim online transportation services. The sampling technique used is non-probability sampling with the purposive sampling method, and the sample size is 215 respondents. Data collection was conducted through a questionnaire, and the analytical tool used is AMOS version 22 with Structural Equation Modeling (SEM) data analysis technique. The results of this study show that social media marketing has a positive and significant influence on brand awareness, electronic word of mouth has a positive and significant influence on brand awareness, advertising effectiveness has a positive and significant influence on brand awareness, brand awareness has a positive and significant influence on purchase intention, social media marketing has a positive and significant influence on purchase intention, Electronic word of mouth has a positive and significant influence on purchase intention, advertising effectiveness has a positive but not significant influence on purchase intention, brand awareness can partially mediate the influence of social media marketing on purchase intention, brand awareness can partially mediate the influence of electronic word of mouth on purchase intention, and brand awareness can fully mediate the influence of advertising effectiveness on purchase intention.